Learning Society Management Strategy for Seniors in The Digital Age: Learning Society Management Strategy for Seniors in The Digital Age - Khumsamart, Supattarasak; Nakrot, Surimart; Nakrot, Surimart; Seesuay, Jantraporn; Sroisang, Chatchapong (RATANABUTH JOURNAL, 2024)
In the modern world, there is rapid development like the rotation of the earth that never stops. Developing learning to keep up with the world is one thing that is necessary today. Whether in technology, society, knowledge and abilities must be equal. No matter what age you are, children, young people, adults, and the elderly. But one thing that you must be aware of carefully is being deceived in various forms in terms of property, money, knowledge, and news that are important in life. It can be seen that technology is useful. But if we use it inappropriately Not knowing sufficiency in use Things that are beneficial can become harmful and have a negative impact on one’s life. Therefore, strategies for managing a learning society for the elderly in the digital age Because nowadays with advanced technology The role of the internet and mobile phones As a result, everyone must adapt in order to keep up with the rapidly evolving era of technology. Learning digital skills is important for every human being, including the elderly. Therefore, it is important to know how to use and use technology appropriately and mindfully in order to be the best and most beneficial path. Therefore, the learning society management strategy For seniors in the digital age It drives measures to support the aging society and longevity of Thai people in Thailand into effective implementation. In the economic aspect, this includes accounting for innovative equipment to assist in the living of the elderly. Environmental aspect includes issuing regulations for local administrative organizations. Carry out a mission of technology and innovation to improve the quality of life of the elderly. In health, it includes promoting technology and innovation systems that help take care of the elderly’s health, and in society, it includes creating learning innovations to increase work skills and life skills.